2011
DOI: 10.1017/s1463423611000016
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods service evaluation of a pilot functional electrical stimulation clinic for the correction of dropped foot in patients with chronic stroke

Abstract: Aim: To undertake a service evaluation of the pilot Lothian functional electrical stimulation (FES) clinic using both quantitative and qualitative methods and clinical practice reflection. Background: Clinical guidelines recommend that FES, for the management of dropped foot after stroke, is delivered by a specialist team. However, little detail is provided about the structure and composition of the specialist team or model of service delivery. A pilot Lothian FES clinic was developed to explore the clinical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
(17 reference statements)
0
2
0
1
Order By: Relevance
“…FES uses electrical pulse trains on the muscle or peripheral nervous system to trigger a controlled tetanic muscle contraction [9,10,[19][20][21]. The shape of the individual pulses that make up the electric pulse trains has an effect on the muscle response.…”
Section: Fes Techniquementioning
confidence: 99%
“…FES uses electrical pulse trains on the muscle or peripheral nervous system to trigger a controlled tetanic muscle contraction [9,10,[19][20][21]. The shape of the individual pulses that make up the electric pulse trains has an effect on the muscle response.…”
Section: Fes Techniquementioning
confidence: 99%
“…Ряд исследований свидетельствует о статистически значимом улучшении скорости ходьбы во время проведения 10-минутного теста ходьбы (10 min walking test) как при отдельном использовании аппарата ФЭС, так и в сочетании с традиционной реабилитацией [30][31][32]. Результаты другого исследования показали статистически значимое повышение скорости ходьбы и улучшение последовательности шага после 6 мес применения ФЭС (p < 0,001) [33].…”
Section: сравнительная характеристика эффективности функциональной электростимуляции и голеностопного ортезаunclassified
“…In our independent analysis, after discussions with clinicians at the National Institute of Orthopaedically Handicapped (NIOH) at Kolkata, we found that very limited options (like conventional physiotherapy) are available for the rehabilitation of stroke survivors in India. The recent literature on advances in stroke rehabilitation and the National Health Science (NHS-UK) guidelines on neurological disorders recommend the use of FES in correcting the problem of foot drop 7 . The operating cost is the most important determinant for this rehabilitation technology from the perspective of the population of developing countries.…”
Section: A Task 1: Need Identifi Cation and Conceptionmentioning
confidence: 99%